Always hungry? ebook Conquer cravings, retrain your fat cells, and lose weight permanently. - Ludwig, David (2016)
Leading Harvard Medical School expert and "obesity warrior" ( Time magazine ) Dr. David Ludwig rewrites the rules on weight loss, diet, and health in this guide to retraining your cells and reclaiming your health for life. Forget everything you've been taught about dieting. In Always Hungry? , renowned endocrinologist Dr. David Ludwig explains why traditional diets don't work and presents a radical new plan to help you lose weight without hunger, improve your health, and feel great. For over two decades, Dr. Ludwig has been at the forefront of research into weight control. His groundbreaking studies show that overeating doesn't make you fat; the process of getting fat makes you overeat. That's because fat cells play a key role in determining how much weight you gain or lose. Low-fat diets work against you by triggering fat cells to hoard more calories for themselves, leaving too few for the rest of the body. This "hungry fat" sets off a dangerous chain reaction that leaves you feeling ravenous as your metabolism slows down. Cutting calories only makes the situation worse by creating a battle between mind and metabolism that we're destined to lose. You gain more weight even as you struggle to eat less food. Always Hungry? turns dieting on its head with a three-phase program that ignores calories and targets fat cells directly. The recipes and meal plan include luscious high-fat foods (like nuts and nut butters, full-fat dairy, avocados, and dark chocolate), savory proteins, and natural carbohydrates. The result? Fat cells release their excess calories, and you lose weight - and inches - without battling cravings and constant hunger. This is dieting without deprivation. Forget calories. Forget cravings. Forget dieting. Always hungry? reveals a liberating new way to tame hunger and lose weight for good.